Peningkatan kualitas produk dan pemasaran kue bhoi sebagai kue tradisional Aceh (Improving the quality of production and marketing of bhoi cake as traditional Aceh cake) - Sulastri, S; Nazar, Muhammad; Zatya, Ismi (Universitas Syiah Kuala, 2023)
Bhoi cake is one of Aceh's traditional cakes which is served at every traditional wedding party and other events as a side dish to the main meal. Community service activities have been carried out in the Syiah Kuala District, namely Gampong Peurada. This service aims to increase the durability of bhoi cakes, change the packaging to be more attractive and help producers to be able to market bhoi cake products online in e-commerce. This service begins with a survey of the initial conditions of bhoi cakes including post-production durability, packaging, and marketing systems. Before the dedication activity was carried out, the bhoi cake only lasted 5-7 days, after that the bhoi cake would grow mold which indicated that the cake was no longer fit for consumption. Bhoi cakes are packaged in ordinary transparent plastic and marketing is only across villages for the needs of traditional events. This service method uses production, packaging, and marketing assistance. After the dedication, it was obtained that the bhoi cake had a shelf life of 1 month and had a good texture. The bhoi cake packaging is more attractive and modern and is accompanied by the brand name, composition, and production date information. Bhoi cakes can now be purchased by consumers online at the e-commerce link provided.